Determinants of Medication Adherence Among Elderly Patients: A Multivariate Study at PKU Muhammadiyah Gamping Yogyakarta - Octavia, Mega; Susana, Yolanda Putri; Rahajeng, Bangunawati (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Adherence to medication in elderly patients is crucial to support their health, as many suffer from chronic non-communicable diseases requiring long-term treatment. The complexity and volume of medications can lead to patient fatigue. Identifying factors that affect adherence is key to addressing these challenges. This study aims to identify the factors influencing medication compliance among elderly patients at PKU Muhammadiyah Gamping Hospital’s outpatient clinic. This quantitative, cross-sectional study involved 80 elderly patients at the internal medicine clinic, selected through accidental sampling. Data was collected using the MMAS-8 (Modified Morisky Adherence Scale-8) and additional questionnaires to determine the factors influencing therapy adherence, analyzed through multiple linear regression. Results showed that compliance was low in 21.3% of patients, moderate in 43.8%, and high in 35.0%. Statistical analysis found significant influences from education level (p<0.05), illness duration (p<0.05), knowledge level (p<0.05), health service access (p<0.05), family support (p<0.05), healthcare workers’ role (p=0.029), and treatment motivation (p<0.05). Compliance among elderly patients at PKU Muhammadiyah Gamping Hospital falls in the moderate category, with these factors explaining 75.6% of adherence levels.